The potential of resilient carbon dynamics for stabilizing crop reproductive development and productivity during heat stress. (22nd February 2021) - Ferguson, John N.; Tidy, Alison C.; Murchie, Erik H.; Wilson, Zoe A.
Abstract: Impaired carbon metabolism and reproductive development constrain crop productivity during heat stress. Reproductive development is energy intensive, and its requirement for respiratory substrates rises as associated metabolism increases with temperature. Understanding how these processes are integrated and the extent to which they contribute to the maintenance of yield during and following periods of elevated temperatures is important for developing climate‐resilient crops. Recent studies are beginning to demonstrate links between processes underlying carbon dynamics and reproduction during heat stress, consequently a summation of research that has been reported thus far and an evaluation of purported associations are needed to guide and stimulate future research. To this end, we review recent studies relating to source–sink dynamics, non‐foliar photosynthesis and net carbon gain as pivotal in understanding how to improve reproductive development and crop productivity during heat stress. Rapid and precise phenotyping during narrow phenological windows will be important for understanding mechanisms underlying these processes, thus we discuss the development of relevant high‐throughput phenotyping approaches that will allow for more informed decision‐making regarding future crop improvement. Abstract : Yield limitations due to heat stress often result from perturbations to reproductive development and carbon dynamics. We review the link between these processes during heat stress and highlight source–sink dynamics, non‐foliar photosynthesis and net carbon gain as key targets for climate‐resilient crop development.